Electron acoustic solitons in the presence of an electron beam and superthermal electrons - Devanandhan, S.; Singh, S.V.; Lakhina, G.S.; Bharuthram, R. (My University, 2011)
Arbitrary amplitude electron acoustic solitons are studied in an unmagnetized plasma having cold electrons and ions, superthermal hot electrons and an electron beam. Using the Sagdeev pseudo potential method, theoretical analysis is carried out by assuming superthermal hot electrons having kappa distribution. The results show that inclusion of an electron beam alters the minimum value of spectral index, k , of the superthermal electron distribution and Mach number for which electron-acoustic solitons can exist and also changes their width and electric field amplitude. For the auroral region parameters, the maximum electric field amplitudes and soliton widths are found in the range (30–524)mVm−1 and (329–729)m, respectively, for fixed Mach number M =1.1 and for electron beam speed of (660–1990) km s−1.
Keywords: Acoustic solitons; Sagdeev pseudo potential method; Magnetosphere